Validity Analysis of Learners' Self- Efficacy Instrument Using Rasch Model - Setiawati, Setiawai; Suryana, Dodi; Amartya, Shafa (Psikopedagogia, 2023)
The issue of items that are not independent, not linear, do not have value accuracy and missing data errors, thus the research aims to test the analysis of the construct validity of the self-efficacy instrument, the research uses a quantitative approach with a cross sectional survey design, then the validity analysis uses the Rasch model with the Winsteps version 3.73 application. The results of this study are (1) all items of the Self-efficacy revealing instrument meet the standard criteria as a measuring instrument. (2) Cronbach Alpha as a measure of the interaction between the person and the item as a whole, has a value that is included in the good category. (3) Person Reliability as an indicator of the constancy of respondents' answers, the results of its value are included in the sufficient category. While (4) Item Reliability as an indicator of the quality of items on the instrument, its value is included in the excellent category. (5) The average difficulty level of items is below the ability of junior high school students, so it is easy to understand. The instrument can be used as a need assessment for students in measuring self-efficacy ability curately